BS35 Pontin regulates cardiac remodelling by modulating the hippo pathway in cardiomyocytes. (4th June 2021) - Lestari, Bayu; Bui, Thuy Anh; Prehar, Sukhpal; Zi, Min; Triastuti, Efta; Nugroho, Ardiansah Bayu; Potter, Ryan; Stafford, Nicholas; Cartwright, Elizabeth; D'Souza, Alicia; Oceandy, Delvac
Abstract : The development of heart failure (HF) is characterised by adverse remodelling events such as hypertrophy, fibrosis, and apoptosis, which together can alter the size, shape, and function of the heart. Identification of new factors that are involved in these processes is important in developing new strategies for HF therapy. Pontin (RUVBL1) is a member of the AAA+ protein family that regulates embryonic zebrafish heart development; however, its role in the adult mammalian heart is unknown. Our previous studies have found that Pontin can induce the activity of the major downstream effector of the Hippo pathway YAP, which is known to play an essential role in mediating cardiac remodelling. Thus, in this study, we aim to investigate the roles of Pontin in mediating adverse cardiac remodelling. Pontin knock-down (KD) and overexpression (OE) in primary neonatal rat cardiomyocytes (NRCM) were achieved by siRNA-mediated gene silencing and adenoviral-mediated overexpression, respectively. We found that Pontin KD negatively modulates NRCM proliferation, represented by a significant reduction in Ki67-positive cells and EdU-incorporation compared to control. Moreover, Pontin KD significantly reduces the level of active YAP, nuclear YAP localisation, and YAP transcriptional activity in NRCM. In contrast, Pontin OE induced NRCM proliferation by approximately 1.6 folds as determined by Ki67 staining and EdU incorporation assay. YAP activity and nuclear translocation were also significantly increased following Pontin OE. We also found that Pontin OE reduced cardiomyocyte hypertrophy and apoptosis (TUNEL staining) in response to Angiotensin II stimulation, whereas KD of Pontin increased Angiotensin-stimulated hypertrophy and apoptosis. To study the role of Pontin in vivo, we generated a mouse model with an inducible cardiomyocyte-specific knockout of Pontin (PontinicKO) by crossing Pontinflox/flox mice with αMHC-MerCreMer transgenic mice. Induction of Pontin ablation was achieved by intraperitoneal injection with tamoxifen. We found that PontinicKO mice exhibited a severe cardiomyopathy phenotype at four weeks after tamoxifen injection, which was characterised by a significant reduction of ejection fraction, increased cardiac fibrosis and hypertrophy, and profound cardiomyocyte apoptosis. In conclusion, our study has identified Pontin as a key regulator of cardiac remodelling, likely by modulating the Hippo pathway. Further studies are needed to explore the therapeutic potentials of Pontin in controlling cardiac remodelling. Conflict of Interest: None